Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
first you need to solve the equation
-2m-5m-8=3+(-7)+m
-7m-8=-4+m or -7m-8=m-4
the second choice
also this choice
8 - 7m = -4 + m the fifth one
-2m-5m-8=3+(-7)+m
-7m-8=-4+m or -7m-8=m-4
the second choice
also this choice
8 - 7m = -4 + m the fifth one
To solve this problem, we must simplify the the equation:
Here is the base equation -2m - 5m - 8 = 3 + (-7) + m (Add all like terms):
#1 -2m - 5m - 8 = 3 + (-7) + m (Property of Addition)
#2 -7m - 8 = -4 + m (Most Simplified Equation)
The answer your would be the 2nd one. -7m - 8 = m - 4
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.